Towards a Treatment for Intolerance of Uncertainty in Young People with Autism Spectrum Disorder: Development of the Coping with Uncertainty in Everyday Situations (CUES©) Programme - Rodgers, Jacqui (J Autism Dev Disord, 2016)
Intolerance of uncertainty (IU) is indicated as an important transdiagnostic process variable in a range of anxiety disorders. Anxiety is very common in children with autism spectrum disorders (ASD). This study aimed to develop a parent group based manualised treatment programme for young people with ASD, which focused on IU. An eight session programme was developed and then delivered to 11 parents across three treatment groups, two recruited via a research data base and one via clinical services. Data regarding retention, acceptability and feasibility indicate that the parents valued the programme. Effect size analyses of outcome measures for potential use in larger trial indicate that the programme has promise as a treatment option of your people with ASD and IU.